The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/bioengineering9030115
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Enzymatic Saccharification and Ethanol Production from Rice Straw Using Recycled Ionic Liquid: The Effect of Anti-Solvent Mixture

Abstract: One of the major concerns for utilizing ionic liquid on an industrial scale is the cost involved in the production. Despite its proven pretreatment efficiency, expenses involved in its usage hinder its utilization. A better way to tackle this limitation could be overcome by studying the recyclability of ionic liquid. The current study has applied the Box–Behnken design (BBD) to optimize the pretreatment condition of rice straw through the usage of 1-ethyl-3-methylimidazolium acetate (EMIM-Ac) as an ionic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Expensive reagents characterize the ionic liquid process, and its recirculation is crucial. To reduce the OpEx in the ionic liquid schemes, recirculation of the ionic liquid was proposed by adding anti-solvent to the reactive mixture in a 1:1 by weight ratio followed by centrifugation and evaporation to remove the anti-solvent from the ionic liquid for its subsequent recirculation [ 68 ]. This process allowed more than 10% decrease in OpEx associated with the demand for reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Expensive reagents characterize the ionic liquid process, and its recirculation is crucial. To reduce the OpEx in the ionic liquid schemes, recirculation of the ionic liquid was proposed by adding anti-solvent to the reactive mixture in a 1:1 by weight ratio followed by centrifugation and evaporation to remove the anti-solvent from the ionic liquid for its subsequent recirculation [ 68 ]. This process allowed more than 10% decrease in OpEx associated with the demand for reagents.…”
Section: Resultsmentioning
confidence: 99%
“…The recycling capacity of the IL can help reduce the cost of the pretreatment. The low volatility of IL makes it feasible for recycling studies 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Further, besides the use of inexpensive ILs with a considerable amount of water, biomass loading is utilized, being an important and economically justified parameter for the process. The acceptable rate of biomass loading is 10% in the literature 24 26 . Thus, the application of a high biomass load that gives rise to greater possibilities for the industrial pretreatment process should be taken into consideration 27 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Recent studies have reported the use of [C 2 C 1 im][MeCO 2 ] for improving enzymatic saccharification and ethanol production from rice straw. 15 Additionally, the potential of the perennial grass Pennisetum polystachion as a biofuel source has been investigated with aqueous [C 2 C 1 im][MeCO 2 ] pretreatment. 16 Extraction of lipid from Chlorella vulgaris using high hydrostatic pressure treatment with [C 2 C 1 im][MeCO 2 ] has also been explored.…”
Section: Introductionmentioning
confidence: 99%